2019
DOI: 10.1007/s10853-019-03633-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic understanding and strategies to design interfaces of solid electrolytes: insights gained from transmission electron microscopy

Abstract: Solid electrolytes (SEs) have garnered increased attention for their promise to enable higher volumetric energy density and enhanced safety required for future battery systems. SEs are not only a key constituent in all-solid-state batteries, but also are important "protectors" of Li-metal anodes in next-generation battery configurations, such as Li-air, Li-S, redox flow batteries, among others. The impedance at interfaces associated with SEs, e.g. internal grain/phase boundaries and their interfacial stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 207 publications
0
7
0
Order By: Relevance
“…TEM was employed to further probe: (i) the contact between the Li 3 PS 4 and PEO and (ii) nanocrystalline domains which may exist in these amorphous materials. Lithium thiophosphates are notoriously difficult to study via TEM at room temperature because of their high beam sensitivity. , Therefore, this study utilized cryo-TEM (holder cooled by liquid nitrogen) and low electron dose fluxes (<1000 e – Å –2 s –1 ) to minimize beam damage. Figure a and b show representative cryo-TEM images of Li 3 PS 4 + PEO composites containing 1 and 56 wt % polymer, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…TEM was employed to further probe: (i) the contact between the Li 3 PS 4 and PEO and (ii) nanocrystalline domains which may exist in these amorphous materials. Lithium thiophosphates are notoriously difficult to study via TEM at room temperature because of their high beam sensitivity. , Therefore, this study utilized cryo-TEM (holder cooled by liquid nitrogen) and low electron dose fluxes (<1000 e – Å –2 s –1 ) to minimize beam damage. Figure a and b show representative cryo-TEM images of Li 3 PS 4 + PEO composites containing 1 and 56 wt % polymer, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The above operation was carried out in an argon‐filled glove box. A thin Na 2 O layer was expected to form on the surface of Na metal during the loading process of the TEM‐STM specimen holder into the TEM specimen chamber, which was served as the solid electrolyte in the following in‐situ TEM experiment 54,55 . The W tip with Na 2 O/Na was driven to contact with the HTO sample on the Cu rod, and an appropriate bias voltage was applied on the W tip to drive the sodiation reaction.…”
Section: Methodsmentioning
confidence: 99%
“…A thin Na 2 O layer was expected to form on the surface of Na metal during the loading process of the TEM-STM specimen holder into the TEM specimen chamber, which was served as the solid electrolyte in the following in-situ TEM experiment. 54,55 The W tip with Na 2 O/Na was driven to contact with the HTO sample on the Cu rod, and an appropriate bias voltage was applied on the W tip to drive the sodiation reaction. In order to minimize the influence of the electron beam, the electron beam was blocked except for imaging and video recording during the sodiation process.…”
Section: In Situ Tem Characterizationmentioning
confidence: 99%
“…[213][214][215] The composition of this layer with N and P concentration gradients and their unique spatial distribution acts as an effective passivation layer. [214][215][216] LiPON/LCO interface, its composition, and electronic structure have been also studied by such techniques as X-ray photoemission spectroscopy, scanning transmission electron microscopy (STEM) coupled with electron energy loss spectroscopy (EELS). It was observed that the interface of a 10Å layer is usually formed with nitrogen-containing species.…”
Section: Lithium Phosphate Based Electrolytesmentioning
confidence: 99%